Digital health for real-time monitoring of a national immunisation campaign in Indonesia: a large-scale effectiveness evaluation. Issue 12 (10th December 2020) - Jusril, Hafizah; Ariawan, Iwan; Damayanti, Rita; Lazuardi, Lutfan; Musa, Miriam; Wulandari, Suci Melati; Pronyk, Paul; Mechael, Patricia
Abstract : Objective: To assess the contribution of a digital health real-time monitoring platform towards the achievement of coverage targets during a national immunisation campaign in Indonesia. Interventions: A digital health platform was introduced to facilitate real-time reporting and data visualisation. Health workers submitted reports of children immunised each day by geolocation using mobile phones. Automated reports were generated for programme managers at all levels to enable early responses to coverage gaps. Methods: Risk profiles were generated for each district to assess precampaign immunisation programme performance. Digital health platform use and progress towards targets were monitored continuously throughout the campaign. Study outcomes were total coverage and time to achieve full (100%) coverage. Kaplan-Meier, Cox and linear regression analyses were used to estimate the associations and outcomes after adjusting for district risk profiles. A complementary qualitative assessment explored user experiences and acceptance through interviews with vaccinators and programme managers in provinces and districts selected through multistage random sampling. Results: Between August and December 2018, 6462 health facilities registered to use the digital health platform across 28 provinces and 395 districts. After adjusting for precampaign district risk profile and intracampaign delays due to vaccine hesitancy, districts with greater platform utilisation demonstrated higher coverage overall (R 2 =0.28, p<0.0001) and a shorter interval to achieving full coverage (>75% reporting compliance; Risk Ratio 15.4, 95% CI 5.8 to 40.6). Stronger effects were observed among districts experiencing implementation delays due to vaccine hesitancy. Results from 106 key informant interviews conducted in 6 provinces and 18 districts suggest high degrees of acceptability, ease of use and satisfaction. Conclusion: A digital health platform introduced for real-time monitoring of a national immunisation campaign in Indonesia was feasible, well liked and associated with improved problem solving and programme performance, particularly among districts affected by vaccine hesitancy. Trial registration number: ISRCTN10850448 .